Colorectal Cancer in Patient with Functional Gastrointestinal Symptoms - Z. A. Mamieva; E. A. Poluektova; A. L. Kovaleva; O. S. Shifrin; V. P. Sobolev; V. M. Svistushkin; A. I. Ulyanin; A. S. Tertychnyy; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. A clinical observation to highlight the importance of detailed examination in patients with functional gastrointestinal symptoms.Key points. A 28-yo female patient was admitted with complains of left ileal pain, abdominal distention and up to 4-day stool delay. The complaints had long been interpreted as clinical manifestations of irritable bowel syndrome. No significant abnormalities were revealed in outpatient check-up (general and biochemical blood panels, stool test, abdominal ultrasound, oesophagogastroduodenoscopy). Colonoscopy was performed on admission, with diagnosis of rectal adenocarcinoma. The patient had a prompt surgical intervention, repeated courses of polychemotherapy and is currently followed by an oncologist and coloproctologist. No relapse signs have been reported.Conclusion. Patients with the complaints satisfying the Rome Criteria Revision IV for functional gastrointestinal diseases should have a thorough examination as per recommendations of the Russian Gastroenterological Association and Russian Association of Coloproctologists.